Polychemotherapy for early breast cancer: an overview of the randomised trials - Early Breast Cancer Trialists' Collaborative Group (Elsevier, 1998)
Background There have been many randomised trials of adjuvant prolonged polychemotherapy among women with early breast cancer, and an updated overview of their results is presented.